A rare care of Lomentospora prolificans sternal wound infection post aortic valve replacement—an approach to surgical management. Issue 3 (25th March 2023) - Chan, Stephanie; Kemp, Ursula; Peeceeyen, Sheen C
Abstract: A 77-year-old woman underwent surgical aortic valve replacement via hemisternotomy. Her post-operative course was unremarkable. Owing to travel and contact restrictions during the COVID pandemic, she was unable to attend routine follow up. She continued review with her local medical officer in regional New South Wales. Post 6 months following her index surgery, she was referred to the Infectious Disease Clinic of her local hospital with a non-healing lesion at the base of her hemi-sternotomy wound. Computed tomography revealed a deep sternal wound infection which extended deep to bone. She was admitted to hospital for treatment. The primary pathogen identified was Lomentospora prolificans—a dangerous fungus that affects immunosuppressed patients. Strong antifungal and adjunctive antibiotics did not contribute much to clearance of infection. Radical surgical debridement was required to obtain clean tissue margins.